Handwashing practice among dental students: lessons unlearned from the COVID-19 pandemic - Eliane García Mato; Fátima Buceta Gamallo; Lucía Sande López; Iván Varela Aneiros; Márcio Diniz Freitas; Jacobo Limeres Posse; Pedro Diz Dios; Berta Rivas Mundiña (BMC Medical Education)
Abstract Background Handwashing is essential for reducing the risk of cross-infection in the dental setting, as evidenced by the heightened significance of this practice during the COVID-19 pandemic. Objectives The extent of adherence to handwashing in the dental setting in the post-COVID-19 phase remains unclear, particularly regarding the pandemic’s impact on this practice among dental students. This inquiry constitutes the primary objective of the present study. Materials and methods A cross-sectional study was designed involving 100 randomly selected undergraduated dental students at the Santiago de Compostela University (Spain). In 2023, the handwashing procedures performed by students at the end of practical classes were recorded through direct observation. The variables analyzed were: duration of the procedure, cleaning agent used, and the location of handwashing. Results were compared with those obtained from a similar study conducted in 2015, prior to the COVID-19 outbreak. Results In 2023, 29% of students washed their hands after practical classes, compared to 42% in 2015 (p = 0.046). No students adhered the WHO handwashing recommendations. Among senior students, the percentage practicing handwashing increased (p = 0.019), as did the duration of the procedure (p = 0.013), compared to mid-senior students. A higher percentage of students engaged in handwashing (p = 0.01) and for a longer duration (p = 0.038) at the conclusion of clinical training session compared to preclinical simulation session. Conclusions Despite the impact of the COVID-19 pandemic, handwashing is not a standard practice among dental students. Therefore, it is imperative to implement educational measures that promote genuine adherence to this hygiene practice.